Mesenchymal stem cells attenuate peripheral neuronal degeneration in spinocerebellar ataxia type 1 knockin mice. Issue 3 (28th December 2015) - Mieda, Tokue; Suto, Nana; Iizuka, Akira; Matsuura, Serina; Iizuka, Haku; Takagishi, Kenji; Nakamura, Kazuhiro; Hirai, Hirokazu
Abstract : Spinocerebellar ataxia type 1 (SCA1) is a devastating neurodegenerative disorder in which an abnormally expanded polyglutamine tract is inserted into causative ataxin‐1 proteins. We have previously shown that SCA1 knockin (SCA1‐KI) mice over 6 months of age exhibit a degeneration of motor neuron axons and their encasing myelin sheaths, as reported in SCA1 patients. We examined whether axon degeneration precedes myelin degeneration or vice versa in SCA1‐KI mice and then attempted to mitigate motor neuron degeneration by intrathecally administering mesenchymal stem cells (MSCs). Temporal examination of the diameters of motor neuron axons and their myelin sheaths revealed a decrease in diameter of the axon but not of the myelin sheaths in SCA1‐KI mice as early as 1 month of age, which suggests secondary degeneration of the myelin sheaths. We injected MSCs into the intrathecal space of SCA1‐KI mice at 1 month of age, which resulted in a significant suppression of degeneration of both motor neuron axons and myelin sheaths, even 6 months after the MSC injection. Thus, MSCs effectively suppressed peripheral nervous system degeneration in SCA1‐KI mice. It has not yet been clarified how clinically administered MSCs exhibit significant therapeutic effects in patients with SCA1. The morphological evidence presented in this current mouse study might explain the mechanisms that underlie the therapeutic effects of MSCs that are observed in patients with SCA1. © 2015 Wiley Periodicals, Inc. Abstract : Mesenchymal stem cells ameliorate degeneration of both neurons and myelin in the spinal cord of aged SCA1 knockin mice.